2014
DOI: 10.1111/bph.12791
|View full text |Cite
|
Sign up to set email alerts
|

CFTR potentiators partially restore channel function to A561E‐CFTR, a cystic fibrosis mutant with a similar mechanism of dysfunction as F508del‐CFTR

Abstract: Background and Purpose Dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) Cl− channel causes the genetic disease cystic fibrosis (CF). Towards the development of transformational drug therapies for CF, we investigated the channel function and action of CFTR potentiators on A561E, a CF mutation found frequently in Portugal. Like the most common CF mutation F508del, A561E causes a temperature‐sensitive folding defect that prevents CFTR delivery to the cell membrane and is associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 69 publications
3
57
1
Order By: Relevance
“…To explore the specificity of CFFT‐004, we tested its effects on A561E, another class II‐III‐VI CF mutation (Veit et al, ) found in NBD1 with defects closely comparable to those of F508del‐CFTR (Mendes et al, ; Wang et al, ). Figures and demonstrate that when BHK cells expressing either F508del‐ or A561E‐CFTR were grown at 37°C, no mature protein was produced and no channel activity was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the specificity of CFFT‐004, we tested its effects on A561E, another class II‐III‐VI CF mutation (Veit et al, ) found in NBD1 with defects closely comparable to those of F508del‐CFTR (Mendes et al, ; Wang et al, ). Figures and demonstrate that when BHK cells expressing either F508del‐ or A561E‐CFTR were grown at 37°C, no mature protein was produced and no channel activity was observed.…”
Section: Resultsmentioning
confidence: 99%
“…In (A) and (B), some data were originally published in Wang et al . () (A, n = 4; B, n = 5); other data are newly acquired. Other details as in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4C shows the mean of current densities at 0 mV during stimulation of F508del-CFTR by Fsk + Gst at 22°C ( n = 6) or 35°C ( n = 5). According to the literature (Wang et al, 2011, 2014; Liu et al, 2012) and contrary to the CFTR response obtained at 22°C, only a small transient current is recorded at physiological temperature. These results show that whole-cell CFTR currents can be studied at 37°C using APC, allowing drug effects to be studied under physiological conditions.…”
Section: Resultsmentioning
confidence: 89%
“…1 and 3). As described in the Materials and Methods, we made prolonged, uninterrupted recordings at room temperature, at which ∆F508‐CFTR channel activity is stable ( e.g ., 44), to accurately determine channel number and acquire sufficient transitions to quantify channel gating. The single‐channel current amplitude ( i ) of these 4 deletion mutants is similar to that of WT CFTR (Fig.…”
Section: Resultsmentioning
confidence: 99%